Edukasi Pemanfaatan Pupuk Organik terhadap Usaha Tani Komoditas Padi di Desa Karangan, Trenggalek - Setyawati, Tri; Jannah, Rika Miftakhul; Widiyono, Wahyu; Artini, Widi; Arissaryadin; Andajani, Wiwiek (JATIMAS : Jurnal Pertanian dan Pengabdian Masyarakat, 2024)
The majority of people in Karangan Village work as rice farmers. The majority of farmers use chemical fertilizers, which, in the long term, can reduce soil fertility and rice productivity. In addition, chemical fertilizers are also scarce and prices are increasing. Therefore, the use of organic fertilizers from cow dung waste can be an alternative to reduce dependence on expensive and scarce chemical fertilizers. Organic fertilizers contain organic materials that can increase soil fertility. Community service activities carried out in Karangan Village aim to provide practical solutions to various problems faced by the community, especially in the agricultural sector and community development. The implementation of this program went smoothly, and most of its objectives were achieved. The community gained new knowledge about organic fertilizers and sustainable agricultural techniques. The results of the demonstration in the field showed an increase in crop yields, which encouraged farmers to adopt this technology. In addition, cooperation activities to improve village infrastructure also increased the accessibility of agricultural land, which had a positive impact on the daily productivity of farmers. Masyarakat di Desa Karangan mayoritas bekerja sebagai petani padi. Mayoritas petani menggunakan pupuk kimia yang dalam jangka panjang dapat menurunkan kesuburan tanah dan produktivitas padi. Selain itu, pupuk kimia juga mengalami kelangkaan dan peningkatan harga. Oleh karena itu, penggunaan pupuk organik dari limbah kotoran sapi dapat menjadi alternatif untuk mengurangi ketergantungan pada pupuk kimia yang mahal dan langka. Pupuk organik mengandung bahan organik yang dapat meningkatkan kesuburan tanah. Kegiatan pengabdian yang dilakukan di Desa Karangan bertujuan untuk memberikan solusi praktis bagi berbagai masalah yang dihadapi masyarakat, khususnya dalam sektor pertanian dan pengembangan komunitas. Pelaksanaan program ini berjalan lancar dan sebagian besar tujuannya tercapai. Masyarakat memperoleh pengetahuan baru tentang pupuk organik dan teknik pertanian berkelanjutan. Hasil dari demonstrasi di lapangan menunjukkan peningkatan hasil panen, yang mendorong petani untuk mengadopsi teknologi ini. Selain itu, kegiatan gotong royong untuk memperbaiki infrastruktur desa juga meningkatkan aksesibilitas lahan pertanian, yang berdampak positif pada produktivitas harian para petani.